Adjunctive brexpiprazole in patients with major depressive disorder and anxiety symptoms: an exploratory study. Issue 10 (24th July 2016) - Davis, Lori L.; Ota, Ai; Perry, Pamela; Tsuneyoshi, Kana; Weiller, Emmanuelle; Baker, Ross A.
Abstract: Background: Major depressive disorder (MDD) with concurrent anxiety symptoms may signal a difficult‐to‐treat patient. Brexpiprazole is a serotonin–dopamine activity modulator: a partial agonist at 5‐HT1A and dopamine D2 receptors at similar potency, and an antagonist at 5‐HT2A and noradrenaline alpha1B/2C receptors. The objective of this Phase IIIb study was to explore effectiveness, safety, and tolerability of brexpiprazole adjunctive to antidepressant (ADT) monotherapy in patients with MDD and anxiety symptoms (NCT02013531). Methods: Patients with MDD, Hamilton Anxiety Rating Scale (HAM‐A) total score ≥ 20, and inadequate response to current ADT received open‐label brexpiprazole 1–3 mg day −1 (target dose 2 mg day −1 ) + ADT for 6 weeks. Efficacy endpoints included change from baseline at Week 6 in Montgomery–Åsberg Depression Rating Scale (MADRS) total score, HAM‐A total score, and Sheehan Disability Scale (SDS). Safety and tolerability assessments included adverse events (AEs). Results: Of 37 participants enrolled, 32 (86.5%) completed the study. Baseline mean ( SD ) MADRS total score was 30.1 (5.1); mean HAM‐A total score was 26.9 (5.0). Improvements from baseline were observed at Week 6 for least squares mean change in MADRS total score (−19.6, p < .0001 vs. baseline), HAM‐A total score (−17.8, p < .0001) and mean ( SD ) SDS mean score [−3.6 (2.6)]. Brexpiprazole was well tolerated. The most frequent treatment‐emergent AEs were increased appetite (13.5%) and diarrhea, dry mouth, and dizziness (all 10.8%). Conclusions: These open‐label results support the anxiolytic effects of adjunctive brexpiprazole in the treatment of patients with MDD. Abstract : Anxiety symptoms are common in patients with major depressive disorder (MDD) and may signal more difficult‐to‐treat patients. A Phase IIIb open‐label study explored brexpiprazole adjunctive to antidepressant monotherapy for participants with MDD and anxiety symptoms who had an inadequate response to their current antidepressant. Anxiety and depressive symptoms and overall functioning improved over the 6‐week study, and brexpiprazole was well tolerated.